Penerapan Prinsip Good Governance dalam Pengelolaan Desa Wisata Sendang di Kabupaten Wonog - Indra Putri Ardilla; Asal Wahyuni Erlin Mulyadi (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2022)
BUMDes Sendang Pinilih manages 2 business units, but the tourist village has superior income compared to the kios online business. Thanks to the existence of a tourist village, it is able to bring Sendang village to be a brilliant village nomination at 11th nationally and is able to improve the village economyThis research explains the application of good governance principles in the management of Sendang tourism village in Wonogiri Regency with indicators of accountability, transparency, community participation and rule of law. Data were obtained through interviews and also sessions of documentation, while the technique of determining informants with the purposive sampling is to help determining the informants according to certain criteria. Data validity, namely source triangulation, is done by comparing data from different source interviews and then analyzing and drawing conclusions and confirming with data from documentation. Data analysis was done interactively through three stages, namely data reduction, data presentation and also data verification. The results of the application of the principles of good governance are the implementation of accountability with the regeneration of the 2019 management, the existence of ADRT which regulates the duties and responsibilities, the monitoring of performance through regular meetings and accountability reports. Transparency is realized through access to information through the Sendang Village and BUMDes websites, quarterly meetings and accountability reports. The community participates as administrators to BUMDes employees, trades, maintains cleanliness and promotes tourism villages through social media, but not many people are willing to express their aspirations. The indicator of the rule of law is realized by the mechanism for recruiting and dismissing administrators according to ADRT, problems are resolved internally by BUMDes and reported to the village head and supervisors, tourism village policies accommodate the needs of the Sendang village community and verbal sanctions are applied or dismissal of BUMDes administrators in accordance with applicable rules.